Reduced snow cover alters root‐microbe interactions and decreases nitrification rates in a northern hardwood forest. Issue 12 (2nd December 2016) - Sorensen, Patrick O.; Templer, Pamela H.; Christenson, Lynn; Duran, Jorge; Fahey, Timothy; Fisk, Melany C.; Groffman, Peter M.; Morse, Jennifer L.; Finzi, Adrien C.
Abstract: Snow cover is projected to decline during the next century in many ecosystems that currently experience a seasonal snowpack. Because snow insulates soils from frigid winter air temperatures, soils are expected to become colder and experience more winter soil freeze‐thaw cycles as snow cover continues to decline. Tree roots are adversely affected by snowpack reduction, but whether loss of snow will affect root‐microbe interactions remains largely unknown. The objective of this study was to distinguish and attribute direct (e.g., winter snow‐ and/or soil frost‐mediated) vs. indirect (e.g., root‐mediated) effects of winter climate change on microbial biomass, the potential activity of microbial exoenzymes, and net N mineralization and nitrification rates. Soil cores were incubated in situ in nylon mesh that either allowed roots to grow into the soil core (2 mm pore size) or excluded root ingrowth (50 μm pore size) for up to 29 months along a natural winter climate gradient at Hubbard Brook Experimental Forest, NH (USA). Microbial biomass did not differ among ingrowth or exclusion cores. Across sampling dates, the potential activities of cellobiohydrolase, phenol oxidase, and peroxidase, and net N mineralization rates were more strongly related to soil volumetric water content ( P  <   0.05; R 2  = 0.25–0.46) than to root biomass, snow or soil frost, or winter soil temperature ( R 2  < 0.10). Root ingrowth was positively related to soil frost ( P  <   0.01; R 2  = 0.28), suggesting that trees compensate for overwinter root mortality caused by soil freezing by re‐allocating resources towards root production. At the sites with the deepest snow cover, root ingrowth reduced nitrification rates by 30% ( P  <   0.01), showing that tree roots exert significant influence over nitrification, which declines with reduced snow cover. If soil freezing intensifies over time, then greater compensatory root growth may reduce nitrification rates directly via plant‐microbe N competition and indirectly through a negative feedback on soil moisture, resulting in lower N availability to trees in northern hardwood forests.